Maintaining exceptionality: Interrogating gestational limits for abortion. (June 2022) - Millar, Erica
Gestational limits on abortion are often seen as a condition for decriminalisation. Focusing on the final reports of three institutional law reform inquiries into abortion in Australia, this article argues that gestational limits were recommended through foreclosing the subject position of the unwillingly pregnant woman who experiences gestational time as a threat to her bodily integrity and imagined future. Structural features of law reform commissions tethered models of decriminalisation to the era of criminalisation. Abortion was also rendered meaningful in the reports through discursive tropes that centred foetal viability and constructed later abortion in terms of a delay that required explanation, with the medico-judicial categories used to explain this delay – which distinguished between 'medical' and 'psychosocial' abortions – recentring the decision-making authority of doctors. Gestational limits on abortion rearticulate the exceptionality of abortion, reinscribing the illegitimacy of abortion and the people who have them, at least at later stages of pregnancy.